Változatok a középszintre, avagy a magyar középszinttelenség - Zongor, Gábor (Tér és Társadalom, 1999)
After the change of regime the main characteristic of the Hungarian administration structure is its dividing. The law of local governments has lead to one of the most important and most exciting changes in the process of change of political system. The primary aim of the legislation was the "liberation" of settlements, and in connection with the íssue of intermediate levei it concentrated to reach a compromise to eliminate the different views, instead of examining its operability. Functions and tasks of county govemments were defined generally, but it become fairly clear from the regulation that function of new type county govemments – with the one-sided overstatement of the principle of subsidiarity – has limited to the maintaining of institutions are providing public services. Central govemment has forced the foundation of regional organisation only due to negotiations with and expectations of the European Union. So the so-called planning-statistical regíons and its organisations the regional development councils – have been established in the pressure of solid governmental force. Professional infrastructure of regional development councils has been formed very late and enervate, therefore its real activity is quite poor yet. There is an attempt to demolish the counties with the establishment of subregions, as administration units. The several quasi-administrational organisations are the characteristics of intermediate level administration, like organisations of regional development, labour councils, county health conciliation forum, regional committee of tourism. Under present circumstances due to the crowd of different organisations in the intermediate level we can’t say from system rather the lack of system and the lack of intermediate level.